2013
DOI: 10.1002/hyp.10098
|View full text |Cite
|
Sign up to set email alerts
|

Response of water and energy exchange to the environmental variable in a desert-oasis wetland of Northwest China

Abstract: A case study on a desert-oasis wetland ecosystem in the arid region of Northwest China measured the seasonal and interannual variation in energy partitioning and evapotranspiration to analyse the response of water and energy exchange on soil moisture, groundwater, and environmental variables. Energy partitioning showed a clear seasonal and interannual variability, and the process of water and energy exchange differed significantly in the monthly and interannual scales. The net radiation was 7.31 MJ m À2 · day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Regarding the meteorological controls on plant water use, many studies have found fairly good linear relationships at the daily scale between transpiration and radiation and vapour pressure deficit ( VPD ), which are two major controlling factors as shown recently, for example, for plants in a desert‐oasis wetland of northwest China (Liu, Zhao, Wen, & Zhang, ), Scots pine in a boreal, humid Scottish catchment (Wang, Tetzlaff, Dick, & Soulsby, ), and tropical montane cloud forest in São Paulo Brazil (Eller, Burgess, & Oliveira, ). However, at the sub‐daily scale (i.e., hourly), the linear relationships between Ec and environmental variables have been shown to be weaker in most studies (Ma et al, ; Tie, Hu, Tian, Guan, & Lin, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…Regarding the meteorological controls on plant water use, many studies have found fairly good linear relationships at the daily scale between transpiration and radiation and vapour pressure deficit ( VPD ), which are two major controlling factors as shown recently, for example, for plants in a desert‐oasis wetland of northwest China (Liu, Zhao, Wen, & Zhang, ), Scots pine in a boreal, humid Scottish catchment (Wang, Tetzlaff, Dick, & Soulsby, ), and tropical montane cloud forest in São Paulo Brazil (Eller, Burgess, & Oliveira, ). However, at the sub‐daily scale (i.e., hourly), the linear relationships between Ec and environmental variables have been shown to be weaker in most studies (Ma et al, ; Tie, Hu, Tian, Guan, & Lin, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…When soil particles adsorb Mg 2+ and Ca 2+ from the groundwater, this increases the concentration of Na + in the soil solution. Generally, shallow groundwater strongly dilutes ions in the soil solution in riparian wetlands, which is why the ion concentrations are lower than in a saltmarsh wetland (Liu et al, 2014(Liu et al, , 2017(Liu et al, , 2019. Thus, concentration of the soil solution through ET combines with ion adsorption and release to alter hydrochemical characteristics such as the Mg 2+ /SO 4 2− ratio in wetlands.…”
Section: Hydrochemical Characteristicsmentioning
confidence: 99%
“…At the same time, high C, N, and P also mean that there may be little exchange of soil nutrients between the arid wetlands and their external environment. In saline wetlands in arid regions, the irrigation backwater is also one of the main water sources which are rich in salt ions and nutrient elements because of fertilizer application in agricultural activity (Liu et al, 2014(Liu et al, , 2017(Liu et al, , 2019. On the one hand, salt ions and nutrient elements are transported toward the soil surface through capillary rise from shallow groundwater and irrigation water with continuous evapotranspiration, leading to salt accumulation and nutrient enrichment near the soil surface.…”
Section: Density and Storage Of Total C N And Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship is commonly characterized as linear increase of plant water use with increasing moisture within a certain range above which plant water use maintains its potential rate and will be limited mainly by energy (Novák et al, 2005). Noticeably, some studies observed a parabolic relationship between plant water use and soil moisture (Zhao and Liu, 2010) or groundwater level (Liu et al, 2014a).…”
mentioning
confidence: 99%